At Westonci.ca, we provide clear, reliable answers to all your questions. Join our vibrant community and get the solutions you need. Experience the convenience of getting accurate answers to your questions from a dedicated community of professionals. Get quick and reliable solutions to your questions from a community of experienced experts on our platform.
Sagot :
To find the point-slope form of the equation of a line given a slope and a point it passes through, we use the point-slope form formula:
[tex]\[ y - y_1 = m(x - x_1) \][/tex]
Where:
- \( (x_1, y_1) \) is a point on the line,
- \( m \) is the slope of the line.
Given:
- Slope \( m = -13 \)
- Point \( (x_1, y_1) = (5, 7) \)
Substituting the given values into the formula:
[tex]\[ y - 7 = -13(x - 5) \][/tex]
Let's check this against the given options:
A. \( y+5=-13(x+7) \)
This does not match because it has \( y+5 \) and \( x+7 \) instead of \( y-7 \) and \( x-5 \).
B. \( y+7=-13(x+5) \)
This also does not match because it has \( y+7 \) and \( x+5 \) instead of \( y-7 \) and \( x-5 \).
C. \( y-5=-13(x-7) \)
This does not match either because it has \( y-5 \) and \( x-7 \) instead of \( y-7 \) and \( x-5 \).
D. \( y-7=-13(x-5) \)
This matches the equation we derived.
Thus, the correct answer is:
[tex]\[ y - 7 = -13(x - 5) \][/tex]
Hence, the correct option is:
D. [tex]\( y-7=-13(x-5) \)[/tex]
[tex]\[ y - y_1 = m(x - x_1) \][/tex]
Where:
- \( (x_1, y_1) \) is a point on the line,
- \( m \) is the slope of the line.
Given:
- Slope \( m = -13 \)
- Point \( (x_1, y_1) = (5, 7) \)
Substituting the given values into the formula:
[tex]\[ y - 7 = -13(x - 5) \][/tex]
Let's check this against the given options:
A. \( y+5=-13(x+7) \)
This does not match because it has \( y+5 \) and \( x+7 \) instead of \( y-7 \) and \( x-5 \).
B. \( y+7=-13(x+5) \)
This also does not match because it has \( y+7 \) and \( x+5 \) instead of \( y-7 \) and \( x-5 \).
C. \( y-5=-13(x-7) \)
This does not match either because it has \( y-5 \) and \( x-7 \) instead of \( y-7 \) and \( x-5 \).
D. \( y-7=-13(x-5) \)
This matches the equation we derived.
Thus, the correct answer is:
[tex]\[ y - 7 = -13(x - 5) \][/tex]
Hence, the correct option is:
D. [tex]\( y-7=-13(x-5) \)[/tex]
Thank you for visiting our platform. We hope you found the answers you were looking for. Come back anytime you need more information. Your visit means a lot to us. Don't hesitate to return for more reliable answers to any questions you may have. Thank you for choosing Westonci.ca as your information source. We look forward to your next visit.